1990
DOI: 10.1007/bf00166968
|View full text |Cite
|
Sign up to set email alerts
|

Actions of the phosphodiesterase inhibitor zardaverine on guinea-pig ventricular muscle

Abstract: The positive inotropic action of the phosphodiesterase inhibitor zardaverine was investigated in guinea-pig heart muscle. In right papillary muscles, 1-30 microM zardaverine reversibly increased the force of contraction in a concentration-dependent manner. This effect was accompanied by a shortening of contraction and relaxation times. Resting membrane potential was unchanged, whereas action potential amplitude was significantly increased and duration was reduced. In papillary muscles partially depolarised wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

1991
1991
1996
1996

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…type TI in rat liver plasma membranes (Pyne et al, 1986) and cardiac ventricle (Timouyasse et al, 1989); type III in rat adipocytes (Degerman et al, 1987) and in canine and Rhesus monkey cardiac ventricle (Weishaar et al, 1987); type IV in rat liver plasma membranes (Pyne et al, 1987) (0.16,uM) is approximately 10 to 20 fold lower than that reported for type IV PDE of human monocytes (2.7 pM) and canine trachea (1.5 pM) (Brothers et al, 1982;Elliott & Leonard, 1989;Galvan & Schudt, 1990), but only 4.5 fold lower than its IC50 for PDE IV from human neutrophils (Nielson et al, 1990). This discrepancy appears to suggest that multiple rolipram-sensitive isoenzymes exist and that an enzyme with greater sensitivity to rolipram predominates in neutrophils and eosinophils.…”
Section: Discussionmentioning
confidence: 98%
“…type TI in rat liver plasma membranes (Pyne et al, 1986) and cardiac ventricle (Timouyasse et al, 1989); type III in rat adipocytes (Degerman et al, 1987) and in canine and Rhesus monkey cardiac ventricle (Weishaar et al, 1987); type IV in rat liver plasma membranes (Pyne et al, 1987) (0.16,uM) is approximately 10 to 20 fold lower than that reported for type IV PDE of human monocytes (2.7 pM) and canine trachea (1.5 pM) (Brothers et al, 1982;Elliott & Leonard, 1989;Galvan & Schudt, 1990), but only 4.5 fold lower than its IC50 for PDE IV from human neutrophils (Nielson et al, 1990). This discrepancy appears to suggest that multiple rolipram-sensitive isoenzymes exist and that an enzyme with greater sensitivity to rolipram predominates in neutrophils and eosinophils.…”
Section: Discussionmentioning
confidence: 98%
“…Therefore, it is unlikely that the lack of efficiency of the PDE inhibitors in the myocytes isolated from noradrenaline-treated guinea-pig hearts was due to an impairment in the contractile apparatus, or due to an enhanced breakdown of cyclic AMP. The concentration of IBMX giving half maximal inhibition of cardiac PDE is reported as 10 LM (Galvan & Schudt, 1990) in guinea-pig myocardium. It has been shown that prenalterol-treated (Bobik & Little, 1984) and noradrenaline-treated (Reithmann & Werdan, 1988) chick embryo cells have depressed levels of cyclic AMP under P-adrenoceptor stimulation.…”
Section: Discussionmentioning
confidence: 99%
“…3.2%(9)** +29.1+ 6.6%(10)* Isoprenaline (10 gM) + 0.98+ 6.4%(9) + 5.94+ 5.7% (8) Data represent the mean + s.e.mean of n independent determinations shown in parentheses. *P<0.05; **P<0.01; significant facilitation in [3H]ACh output Zardaverine (10 gM for 15 min), a mixed inhibitor of the PDE3 and PDE4 isoenzyme families which selectively hydrolyse cyclic AMP (Galvan & Schudt, 1990), had no significant effect on EFS-evoked ACh release (Figure 8). Moreover, zardaverine (10 gM) did not potentiate the facilitatory effect of isoprenaline (0.1, 1 and 10 uM) or the inhibitory action of PGE2 (0.1 nm to 1 gM) on cholinergic neurotransmission at any concentration studied (Table 1; Figure 8).…”
Section: Effects Of Other Cyclic Amp Elevating Drugs On Efsinduced Acmentioning
confidence: 97%
“…To gain further information on the biochemical mechanism(s) by which isoprenaline enhanced cholinergic neurotransmission in guinea-pig trachea, the effect of a number of cyclic AMP-elevating drugs was evaluated on the release of Zardaverine (10 gM for 15 min), a mixed inhibitor of the PDE3 and PDE4 isoenzyme families which selectively hydrolyse cyclic AMP (Galvan & Schudt, 1990), had no significant effect on EFS-evoked ACh release (Figure 8). Moreover, zardaverine (10 gM) did not potentiate the facilitatory effect of isoprenaline (0.1, 1 and 10 uM) or the inhibitory action of PGE2 (0.1 nm to 1 gM) on cholinergic neurotransmission at any concentration studied (Table 1; Figure 8).…”
Section: Effects Of Other Cyclic Amp Elevating Drugs On Efsinduced Acmentioning
confidence: 99%